PROFIL LITERASI SAINS MAHASISWA CALON GURU MADRASAH IBTIDAIYAH - Rahmawati, Jevi Milda (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
Education is a determining factor for the success of the SDGs program. Education in this era prioritizes mastery of XXI century skills, one of which is scientific literacy. Scientific literacy skills have an important function in the development of an individual in the future because it can influence an individual in decision making. This study aims to determine the scientific literacy profile of preservice teachers of Madrasah Ibtidaiyah (MI) STIT Muhammadiyah Tempurejo Ngawi. The study used a survey technique which was carried out on students who had taken IPA I and IPA II courses. The research instrument was a multiple choice test based on the Test of Scientific Literacy Skills (TOSLS) indicator. The results show that the scientific literacy level of preservice MI teacher students is still low with the value of each indicator being in the very poor category